A root system architecture regulator modulates OsPIN2 polar localization in rice - Yong Li; Meiyan Ren; Yunrong Wu; Lingling Wang; Keju Zhao; Hongsheng Gao; Mengzhen Li; Yu Liu; Jianshu Zhu; Jiming Xu; Xiaorong Mo; Zhongchang Wu; et al. (Nature Communications)
Abstract Ideal root system architecture (RSA) is important for efficient nutrient uptake and high yield in crops. We cloned and characterized a key RSA regulatory gene, GRAVITROPISM LOSS 1 (OsGLS1), in rice (Oryza sativa L.). The gls1 mutant displays an increased root growth angle, longer primary roots, more adventitious roots and greater nutrient uptake efficiency and grain yield in paddy fields. OsGLS1 is strongly expressed in the root tips of seedlings and in leaves at the flowering stage. OsGLS1 encodes a RING finger E3 ubiquitin ligase mainly localizing at the basal plasma membrane (PM) in several root cell types when phosphorylated on its Ser-30 residue. OsGLS1 interacts with, ubiquitinates and promotes the degradation of basally localized PIN-FORMED 2 (OsPIN2) via the 26S proteasome, thus establishing the typical apical PM localization of OsPIN2 and polar auxin transport, ultimately shaping RSA. This previously unidentified OsGLS1-OsPIN2 regulatory pathway will contribute to an optimal RSA for enhancing nutrient efficiency in rice and other crops.